Pemanfaatan Rumput Gajah dan Jerami Padi dalam Pembuatan Pakan Alternatif di Desa Jerukwudel, Gunungkidul - Iinuma, Rikiya; Izzatiddieni, Nabila Nurul; Zahra, Baitia; Haidir, Muhamad Ibnu; Ferusza, Adinda Cahaya; Assalamia, Muqita Putrika; Pramudya, Ravi Mahesa; Dasanto, Bambang Dwi (Direktorat Pengembangan Masyarakat Agromaritim, Institut Pertanian Bogor, 2024)
Farmers in Jerukwudel Village, Gunungkidul, face challenges related to the limited availability of green fodder and the lack of nutritional supplements in their feed. To address these issues, silage and ammoniated feed have been proposed as alternative solutions that not only serve as reserve feed during the dry season but also provide additional nutrition for livestock. This community service program aims to enhance the interest of farmers and livestock keepers in Jerukwudel Village in utilizing and developing agricultural waste as alternative feed during the dry season. The methods implemented in this program include preparation and execution of material dissemination, training, feed provision, monitoring, and evaluation. The innovation in alternative feed production in Jerukwudel Village consists of two types of feed: silage and ammoniated feed. The production of these feed types had not previously been attempted in the village. Results from the socialization indicate that the community in Jerukwudel Village actively participated and engaged in a two-way interaction. The community also gained an understanding of the materials and composition used in feed production, as evidenced by a 21% increase in understanding based on pre-tests and post-tests. The fermentation process for silage and ammoniated feed took 21 days, yielding good results indicated by changes in texture, color, and aroma. These changes signified that the production of alternative livestock feed was successful and ready to be distributed to the local livestock. The alternative feed distribution activities demonstrated positive responses, with the livestock showing a preference for the taste and aroma of these feed types.